Verzeihen, Versöhnen, Vergessen Soziologische Perspektiven - Takemitsu, Morikawa (Kulturen der Gesellschaft, 2018)
Illuminated universally as an anthropological invariable yet hardly yet as a sociological category: the potential the act to forgive has for the social and society theory!